Emotional Intelligence Becomes The Main Predictor of Emotional Labor Ability on Customer Satisfaction - Ginanggih Ginanggih; Joeliaty Joeliaty; Sunu Widianto (Quantitative Economics and Management Studies, 2023)
Emotional intelligence and emotional intelligence refers to the process of regulating feelings and expressions in response to emotion regulation as an authentic display of employees in serving customers. The existing literature has provided strong evidence for the impact of customer-focused emotional work. However, an empirical examination of the mechanisms underlying this relationship is largely different from previous studies. This research focuses on employees' emotional intelligence in regulating emotions to make customers satisfied with the services provided. This article reports on a study examining the role of emotional work in channeling the impact of emotional intelligence on customer satisfaction. Specifically, the study measured the emotional intelligence of service employees and customers with in-depth acting to find out how relational relationships occur. The sample size in this study was 232 respondents. Data analysis was carried out using Structural Equation Model (SEM-PLS) 4.0 with outer model measurements: convergent validity, discriminant validity, reality test, and inner model measurement; Coefficient Determinant of (R2), Significance (t-value) and model fit test using R square, Q square, SRMR, Goodness of Fit Index. Results show that employees who are emotionally intelligent and able to regulate their expressions and feelings will increase the influence on customer satisfaction.